Complementary fasciotomy in patients relaparostomized for peritonitis widespread severe - Comín, Raúl; Manna, Ruben; Pesenti, Dante; Moreno, Eduardo (Cirugía del Uruguay, 1998)
In this work is presented a different surgical technique used in twenty patients showing serious generalized peritonitis of different etiologies. In nineteen of then, the abdomen was left opened end held by a poliuretano mesh and the remain is a chronic eventration as a result of the shutting by second of repeated laparostomy. The technique is very useful to easy the snutting of that abdominal wall and consists of making a complementary fasciotomy on the aponeurosis of the mayor oblique, performed through incisions far away from the original. lt is outstanding its easy technique performance mínimum morbility very good results obtained with the plastic of abdomen, even in chronic eventration.